Determination and validation of pregabalin in bulk and pharmaceutical formulations by reversed phase-high performance liquid chromatography - N. Vidya, D.; Chaithra, R.; P. Senthil Kumar, G.; R. Bhadresh, D. (International Journal of Advanced Chemistry, 2020)
A simple, specific, quick, isocratic Reversed Phase High Performance Liquid Chromatographic method was developed and validated for the analysis of Pregabalin in bulk and 5-different pharmaceutical formulations, the separation was accomplished on a C18, 5μm Reverse Phase column (250 mm × 4.6 mm) using a methanol : water (95:5, v/v) mobile phase. The compound was eluted isocratically at a flow rate of 0.8 ml /min. The UV detector was set at 288 nm for the detection of Pregabalin (PRG). The method was linear over the range of 5-45 μg/ml and validated with respect to accuracy, precision, linearity, and specificity, limit of detection and limit of quantization. Robustness testing was also conducted to evaluate the effect of minor changes to the chromatographic system and to establish appropriate system suitability parameters. This method was used successfully for the quality assessment of 5-different pharmaceutical formulations with good precision and accuracy.
Keywords: Pregabalin; Isocratic System; Validation; RP-HPLC; Different Pharmaceutical Formulations.